Speed-related abilities are similarly improved after sled training under different magnitudes of velocity loss in highly trained soccer players - Grazioli, R.; Loturco, I.; Veeck, F.; Setuain, I.; Zandavalli, L. A.; Inácio, M. Pinto, R. S.; Cadore, E. L. (International Journal of Sports Physiology and Performance, 2023)
Purpose: We examined the effects of two 8-week resisted-sprint training programs under different magnitudes of velocity loss (VL) on the speed-related performance of highly trained soccer players. Methods: Twenty-one soccer players (age: 25.9 [5.4] y) ere randomly assigned to 1 of 2 groups: (1) the "moderate-load group," players who trained with sled loads that induced 15%VL relative to unloaded sprint velocity (n = 11); and (2) the "heavy-load group," players who trained with sled loads that induced 40% VL relative to unloaded sprint velocity (n = 10). Linear sprint (10 m), curve sprint, change-of-direction speed, resisted-sprint performance at 15% VL and 40% VL, and vertical jumping ability were tested pretraining and posttraining. A 2-way repeated measures analysis of variance was used to test for differences between groups. In addition, percentage changes were calculated for speed-related abilities and compared with their respective coefficients of variation to determine whether individual changes in performance were greater than the test variance (ie, "true change"). Results: A main effect of time was detected for 10-m sprint, curve sprint, change-of-direction speed, and 15% VL and 40% VL resisted-sprint times, with significant decreases in sprint times (P = .003, P = .004, P = .05, P = .036, and P = .019, respectively). Jump variables did not change significantly over time. There were no group-by-time interactions for any tested variable (P > .05), but the "true change" analysis revealed meaningful individual changes in both groups. Conclusions: Both moderate- and heavy-sled loading conditions may optimize the development of speed-related abilities in highly trained soccer players. Nevertheless, resisted-sprint training responses may differ meaningfully when assessed on an individual basis.